Age differences in information search: An exploration-exploitation tradeoff model. (September 2015) - Chin, Jessie; Anderson, Evan; Chin, Chieh-Li; Fu, Wai-Tat
Past research often found that older adults searched less in terms of browsing and generating keywords; few studies examined the processes and underlying mechanism that caused the age-related reduction on search. In the current study, about 20 younger and 20 older adults performed ill-defined search tasks with a search box we implemented. In addition to the age differences in the quantities of search, results showed that there were qualitative age differences in allocating resources to exploration and exploitation across tasks varying in the accessibility of target information. Older adults were found to do more exploitation in terms of spending longer time and viewing more information before initiating a new search. However, older adults were adaptive to task environments in terms of reducing the number of websites viewed before revising a keyword and increasing the time spent on initiating a new search in the low accessible task, in which more exploration was preferred. The links between difference in search process and the age differences in cognitive abilities were also discussed.